2009
DOI: 10.1007/s00467-008-1088-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal manifestations in toddlers with Takayasu’s arteritis and malignant hypertension

Abstract: Three children under the age of 3 years presented with malignant hypertension, proteinuria, and acute kidney injury. Takayasu's arteritis was diagnosed on the basis of clinical symptoms of weight loss and low grade fever in conjunction with elevated sedimentation rate and radiographic evidence of aortic and renal artery stenosis. One patient had a renal biopsy which showed arteriolar sclerosis and focal glomerulosclerosis. All three patients required multiple antihypertensive agents, ultimately including angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…In our series, five of 22 (22.7%) patients with renovascular hypertension had mid-aortic syndrome; this prevalence rate of midaortic syndrome is within the previously reported range (20%-48%) (5,21). It has been suggested that renovascular hypertension patients with midaortic syndrome may be appropriate for surgical revascularization (19,22). This might be one explanation for the PTRA procedure failure in some patients in this study.…”
Section: Discussionsupporting
confidence: 79%
“…In our series, five of 22 (22.7%) patients with renovascular hypertension had mid-aortic syndrome; this prevalence rate of midaortic syndrome is within the previously reported range (20%-48%) (5,21). It has been suggested that renovascular hypertension patients with midaortic syndrome may be appropriate for surgical revascularization (19,22). This might be one explanation for the PTRA procedure failure in some patients in this study.…”
Section: Discussionsupporting
confidence: 79%
“…Only a few clinical studies described the development of FSGS in malignant hypertension [12][13][14], and these studies reported that FSGS may occur in primary malignant hypertension with nephrotic-range proteinuria, and may contribute to renal dysfunction. In addition, a few cases of renal artery stenosis with malignant hypertension and nephrotic syndrome have been reported [15][16][17][18][19][20]. In such cases, histopathological examination of the contralateral kidney often shows lesions of FSGS with benign or malignant nephrosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Marks and Tullus for their interest in our report of 3 cases of young children with Takayasu's arteritis (TA) [1]. They raise a cogent point, that, neither European nor American rheumatology societies, include inflammation as a classification criterion for the diagnosis of this rare vasculitis.…”
Section: Sirmentioning
confidence: 94%